The Legal Consequences of Unregistered Prenuptial Agreements: Examining the Implications for Third Parties - Windayanti, Winda; Narsudin, Udin; Natanegara, F. Davy Gunady (International Journal of Latin Notary, 2025)
This article critically examines the legal consequences of unregistered prenuptial agreements under Indonesian law, particularly with respect to their enforceability against third parties. Although Article 29(1) of Law No. 1 of 1974 on Marriage permits the creation of prenuptial agreements prior to marriage and affirms their binding effect beyond the spouses, the absence of formal registration renders such agreements legally invisible to third parties. This legal invisibility undermines the principle of legal certainty (rechtszekerheid), exposing creditors, heirs, and business partners to significant legal and financial risks. Using a doctrinal-normative approach complemented by socio-legal perspectives, the study analyzes statutory frameworks, judicial interpretation and scholarly debates surrounding publicity, contractual freedom, and third-party protection. The findings reveal a tension between private autonomy and public legal order in marital property law, especially where administrative formalities determine enforceability. The study concludes that unregistered agreements, while valid inter partes, fail to fulfill their intended protective function in broader legal relationships. It proposes reforms including the establishment of a centralized national registry, enhanced procedural duties for notaries and marriage registrars, and public education campaigns to increase awareness of registration requirements. These recommendations aim to ensure legal certainty, protect third-party interests, and harmonize Indonesia’s family law regime with international standards of legal transparency and accountability.